An Examination of the Patterns of Substance Use in Activity Spaces and Their Relationship to Problematic Use. Issue 3 (April 2021) - Booth, Jaime M.; Urbaeva, Zhyldyz; Park, Daejun
During adolescence, adolescents are given more freedom to independently interact with a variety of social contexts. The eco-developmental model suggests that the activity spaces where adolescents spend their time affect substance-use behaviors beyond peer influences, and that the relationships may differ based on the adolescent's demographic characteristics. This study examines adolescent patterns of reported substance use across activity spaces to determine whether the patterns of use are related to problematic substance use, and whether the relationships differ based on the participants' race. Cross-sectional survey data from the study, Drug Use Among Young American Indians: Epidemiology and Prediction, 1993-2006 and 2009-2013, were used. Five patterns of adolescent alcohol use and six patterns of adolescent drug use in activity spaces were identified. There were significant differences in the relationship between class membership and problematic substance use by race, suggesting that contexts may be interacting with an adolescent's race to influence use.